COVID-19 and stroke—A global World Stroke Organization perspective. Issue 4 (June 2020) - Markus, Hugh S; Brainin, Michael
The COVID-19 pandemic affecting all parts of the world is having huge implications for stroke care. Not only do stroke patients appear to be more susceptible to severe infection, but the pandemic is having major implications on how we deliver stroke care, while ensuing safety of both our patients and health care professionals. COVID-19 infection itself has also been described as a risk factor for stroke. The World Stroke Organization has been monitoring the impact of the pandemic globally, and has identified an initial marked fall in stroke presentations as well as a widespread impact on stroke services. The pandemic is changing the way we deliver care, and has highlighted the enormous potential of telemedicine in stroke care.